Sensory ataxic neuropathy with dysarthria and ophthalmoparesis (SANDO) syndrome associated with two heterozygous POLG mutations - Sasikumar, Sheetal; Jaisukhalal, Jaisurya (Nepal Journal of Neuroscience, 2022)
Polymerase gamma is a mitochondrial DNA polymerase, that is responsible for the replication of the mitochondrial DNA (mtDNA). It is encoded by the POLG gene, on chromosome 15q25. Various mutations in this gene have been described, with varied phenotypic manifestations. The triad of sensory ataxic neuropathy, dysarthria, and ophthalmoparesis (SANDO) has been reported only in a small group of patients with POLG mutations. We report the case of a male, who presented with phenotype of SANDO syndrome and and was found to have two pathogenic, heterozygous mutations in the POLG gene.